Integrated farming enhances rainwater and soil productivity - Tabo, Ramadjita (2009)
The project team investigated the potential for a number of other high value tree crops for inclusion in the system (in addition to Ziziphus mauritania and Acacia colei, , described in box). Analysis of the data is not yet complete, but the responses of participating farmers in Ghana and Burkina Faso to the SEF suggest that they are delighted at the prospect of a diversified and integrated production system that addresses most of their problems. While the SEF is in many ways a self-contained concept, it has great potential for integration with other promising technologies, such as conservation tillage, conservation agriculture, micro-dose fertilization (involving the application of small quantities of fertilizers at the plantbase) and the ‘Zai’ method of planting in water-retaining pockets. Trials of these techniques are also under way across more than 30 sites in the Volta Basin.